Assessment of processing and polymorphic form Effect on the powder and tableting properties of microcrystalline celluloses I and II (2011)
ABSTRACT: Microcrystalline cellulose I (MCCI) is an excipient used as a diluent, disintegrant, glidant and binder for the production of pharmaceutical tablets. In this work, microcrystalline cellulose II (MCCII) was obtained from cotton fibers by basic treatment with 7.5 N NaOH followed by an acid hydrolysis. MCCI and MCCII materials were processed by wet granulation, dry granulation and spray drying. Either the polymorphic form or processing had no effects on the particle morphology or particle size. However, MCCII powders had a higher porosity, less packing tendency, degree of crystallinity, degree of polymerization and density, but a faster disintegration than MCCI. The tensile strength of MCCI was highly affected by the wet and dry granulation processes. Most of the resulting powder and tableting properties were dependent on the polymorphic form of cellulose, rather than on the processing employed.